Thermal strain in motor sport: effect of protective garments. (December 2018) - Ferri, Ada; Beghini, Giulia; Dotti, Francesca; Bardascino, Angelo
Abstract: The objective of this paper is the assessment of heat shield offered by a racing suit in extreme environmental conditions. The method was based on driving simulations in a climatic chamber, during which thermal strain was monitored by measuring a number of physiological and psychological parameters. It was found that a conventional racing suit offered some protection from heat flow but a greater level of protection could be obtained by a reflective outfit. During the test evaporative cooling was negligible because of poor breathability of the outfit and the seat. In conclusion, it was proven that a conventional racing suit offers protection from extreme environmental conditions but it does not guarantees thermal comfort. Use of reflective elements in the racing suit could be beneficial for thermal protection.